1956
DOI: 10.1104/pp.31.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Photoreversibility of Flower Initiation.

Abstract: Action-spectrum studies have shown that such diverse light-controlled plant responses as flower initiation (1,17,18), internode elongation (2,8,19), leaf expansion (8,19), and seed germination (4,23) the dark period, two short-day plants, soybean (Glycine Max (L.) AMerr. var. Biloxi) and pigweed (Amaranthus caudatus L.), and two long-day plants, barley (Hordeum vulgare L. var. Wintex) and Hyoscyamus niger L., were tested for evidence of the far-red action. A brief irradiation near the middle of an inductive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
2

Year Published

1959
1959
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 22 publications
(38 reference statements)
5
53
0
2
Order By: Relevance
“…In some SD plants, the suppression of flowering by a single R light NB is completely reversible by immediate exposure to FR light (Downs, 1956;Cathey and Borthwick, 1957). In wheat, we found that a single FR exposure after NB had a limited effect on heading time (Fig.…”
Section: Discussion Nb Responses In Sd and Ld Plantsmentioning
confidence: 65%
“…In some SD plants, the suppression of flowering by a single R light NB is completely reversible by immediate exposure to FR light (Downs, 1956;Cathey and Borthwick, 1957). In wheat, we found that a single FR exposure after NB had a limited effect on heading time (Fig.…”
Section: Discussion Nb Responses In Sd and Ld Plantsmentioning
confidence: 65%
“…Again it can be seen that cysteine completely reverses the effects of cobaltous ion upon flowering. Cobaltous ion and far-red reversal of red inhibition: It has been shown by Downs (2) that the inhibition of flowering produced by red light interruption of the dark period may be reversed, to some extent at least, by far-red illumination following this interruption. The effect of cobaltous ion upon this response was studied.…”
Section: Experiments and Results Effect Of Various Salts Of Cobalt Upmentioning
confidence: 99%
“…The length of lag periods has been variously reported to range from about 30 minutes to several hours (5,7,14,15,16 (23) suggested that 2 different radiation-limited steps were involved in anthocyanin synthesis in apple skin, and Hendricks (12) further reported that anthocyanin synthesis in seedlings of Sorghum vulgare requires 2 photoreactions. These are an initial reaction in response to high energy irradiation, and a second reaction involving low intensity red irradiation which is reversible by far-red.…”
Section: Discussionmentioning
confidence: 99%